Preparing and accompanying disadvantaged young people in the world of work - present and future requirements for teachers at vocational schools - Peinemann, Katharina [Verfasser] (My University, 2021)
“The world of work is characterized by a variety of changes, which go hand in hand with changing social and economic requirements (Beck 2010). As a result of an increasing shortage of skilled workers combined with demographic developments that have resulted in an aging population, young people with poor school-leaving qualifications or personal and social problems are now being accepted into vocational training programs in Germany (BMWT 2013; Becker & Allmer 2013). This means that teachers in vocational schools can no longer teach exclusively theoretical content; they must also develop learners’ social and personal skills. Yet such topics are rarely taught in university education or in training programs targeting TVET teaching staff. To address this gap, 65 teachers from 11 vocational schools in Mecklenburg-Western Pomerania were surveyed using a method-mixed research design (quantitative questionnaire and followed by in-depth qualitative interviews comprising a smaller sample of respondents) (Hug 2001) and asked how they deal with the challenges of preparing disadvantaged youth for the labour market, without having received specific training for this purpose. Their responses, which were analysed thematically using qualitative content analysis according to Mayring (Hussy, Schreier, & Echterhoff 2010), shed light on the competencies that TVET teachers need to fulfil their expanded role in supporting disadvantaged youth, as well as how TVET teacher training programs need to be reformed to meet the new requirements.” (author’s abstract; BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; P 1.7 Benachteiligte; P 3.2.3 Lehrer; 370; Berufsschule; Benachteiligter Jugendlicher; Berufsvorbereitung; Übergangssystem; Berufsschullehrer; Professionalisierung; Mecklenburg-Vorpommern